THE IMPORTANCE OF EFFECTIVE COMMUNICATION IN THE ACTIVITIES OF A LAWYER (World Conference on Social Sciences, Law and Public Policy, 2026)
This scientific article analyzes the importance of effective communication in the activities of a lawyer, its role in the formation of relationships in working with clients, participation in court proceedings, and ensuring the effectiveness of legal services. It also highlights how the culture of communication, the professional status of a lawyer, speech skills, psychological approach, and professional ethics influence the role and effectiveness of a lawyer's work.
Keywords: lawyer, communication culture, effective communication, legal service, professional ethics, client relations, legal proceedings, legal culture.